Response to brentuximab vedotin in advanced stage MF/Sézary syndrome with low CD-30 expression: "real-life" data of the German Cutaneous Lymphoma Network. (October 2021) - Blazejak, Christoph; Stranzenbach, René; Klemke, Claus-Detlev; Frenzel, Ann-Kathrin; Mitteldorf, Christina; Nicolay, Jan P.; Wobser, Marion; Schrüfer, Philipp; Stadler, Rudolf; Gosmann, Janika; Wehkamp, Ulrike; Stendel, Sarja; et al.
Abstract : Introduction and objectives: Advanced stage mycosis fungoides/Sézary syndrome (MF/SS) are difficult to treat and associated with an inferior prognosis. Brentuximab vedotin (BV) is a frequently used agent in higher stages, particularly in cases with a high expression of CD30. The ALCANZA trial, which included MF patients with a CD30 expression >10%, demonstrated high response rates and a good tolerability. However, its effectiveness in advanced stage MF/SS syndrome with low CD30-expression (<10%) still has to be systematically evaluated. Therefore, the question is whether an equally good response with BV is achievable in these CTCL cases. Material and methods: Between 2018 - 2020, 32 patients in 11 centres with predominantly advanced MF/SS and low CD-30 expression (<10%) were treated with BV in the recommended dosage, retrospective evaluation of therapy response was done according to the EORTC-ISCL criteria. Results: In all patients (n=32) at least one other systemic therapy preceded BV treatment. The median number of previous treatments was 3. Thirty patients suffering from MF (IB: 2; IIA: 1; IIB: n=18; III: 1; IV: 9; total ≥IIB: 27) and 2 SS patients were analyzed. As a result, 17 of 31 patients (OR: 54.8%) responded to therapy (CR n=4/31 12.9%, PR n=13/31 41.9%) after 6 cycles. The median progression-free interval among patients with OR was 6.4 months (range: 0.5–15.5 months, mean ± SD: 6.4±3.8, n=16). In 37.5% (n=12) the CD-30 Expression was 5-9% and in 62.5% (n=20) CD-30-Expression was <5%. Conclusions: In conclusion, with 54.8% OR, BV in MF/SS with low CD-30 expression (<10%) shows a comparable response rate compared to CTCL with CD-30 expression ≥10% (56-73%) and CR (12.9% vs. 3–35%) but with a lower PFS (6.4 vs. 11 months). In summary, based on this data the treatment of MF/SS with low CD-30 expression with BV seems to be an effective therapeutical option and justifies its use in challenging cases independent of the degree of CD30 positivity.